Subalternity and Resistance: Examining Women’s Experiences in Chimamanda Ngozi Adichie’s Purple Hibiscus - Stanislaus Bayu Kusuma Wardhana (JURNAL PENDIDIKAN BAHASA, 2025)
The portrayal of women in formerly colonized nations is a topic covered by postcolonial feminist theory. In this respect, this study examines how colonialism influenced the lives of women in the third world who endure “double colonization” based on both race and gender. This study uses a postcolonial feminist framework to uncover the themes of female voice and subalternity in Chimamanda Ngozi Adichie’s Purple Hibiscus. This study aims to explore how Adichie portrays female subalternity and resistance in Purple Hibiscus. Employing the concept of subaltern, this study also examines how societal and familial structures marginalize women’s experiences and inhibit their self-expression. Through a close reading of the text, this study highlights the characters’ struggles and journeys toward empowerment, which illustrates the complexities of female identity in a patriarchal society within the contexts of postcolonial Nigeria. Focusing on the experiences of Kambili, Beatrice (Kambili’s mother), and Aunty Ifeoma, this study reveals the multifaceted nature of female resistance within the oppressive system.